Joint impact of BMI, physical activity and diet on type 2 diabetes: Findings from two population‐based cohorts in China. Issue 6 (15th December 2021) - Shen, Qiu‐Ming; Li, Hong‐Lan; Li, Zhuo‐Ying; Jiang, Yu‐Fei; Ji, Xiao‐Wei; Tan, Yu‐Ting; Xiang, Yong‐Bing
Abstract: Aims: Limited epidemiological data on the combined impact of several lifestyle factors on type 2 diabetes (T2D) incidence was reported in Chinese population. This study aimed to examine how combinations of BMI, physical activity and diet relate to T2D incidence and estimate corresponding population attributable risk in the general population. Methods: A total of 56, 691 male and 70, 849 female participants aged 40–74 years old in two population‐based cohorts from the Shanghai Men's and Women's Health Studies were used for analysis. The Cox regression model was used to estimate the association between lifestyle factors collected at baseline and T2D incidence. Multivariable‐adjusted population attributable risks were calculated for specific combinations of lifestyle factors. Results: There were 3315 male and 5925 female incident T2D, with corresponding density incidence rates of 6.39 and 6.04 per 1000 person‐years. If the healthiest group of healthy lifestyle index (HLI) was used as a reference, the hazard ratios (95% confidence intervals) of T2D increased monotonically in men [2.04 (1.75, 2.38); 2.94 (2.53, 3.42); 4.31 (3.66, 5.07)] and women [1.85 (1.64, 2.08); 2.79 (2.49, 3.13); 4.14 (3.66, 4.67)]. One point increase of HLI was related to 35% and 35% lower risk in men and women. About 52.7% and 58.4% cases in men and women could have been avoided if participants had been adherent to a healthy lifestyle of maintaining healthy body weight, eating a healthy diet and keeping physically active. Conclusions: An increased number of healthy lifestyle factors were associated with a decreased risk of T2D in the Chinese population. Future interventions targeted at combined healthy lifestyle factors are needed to reduce the burden of T2D.